2000
DOI: 10.3354/meps204065
|View full text |Cite
|
Sign up to set email alerts
|

On the trophic coupling between protists and copepods in arctic marine ecosystems

Abstract: Grazing experiments were conducted at different seasons with the large Calanus finmarchicus, C. glacialis and C. hyperboreus, and the small Acartia longiremis in Disko Bay, West Greenland and Young Sound, NE Greenland. Female copepods incubated in 200 µm screened natural water preferred large protists. Thus, particularly during the post-bloom period, the relatively large heterotrophic protists (ciliates and heterotrophic dinoflagellates) contributed substantially to the trophic coupling between protists and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
127
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(156 citation statements)
references
References 28 publications
16
127
0
4
Order By: Relevance
“…This corresponds to the data from Cripps and Hill (1998), describing omnivorous feeding as more common in lowchlorophyll environments where copepods of the same genera usually ate the most abundant prey. In response to phytoplankton shortage, copepods may switch to alternate prey including nauplii (Tackx and Polk 1982), ciliates (Atkinson 1996), early developmental stages of other calanoids (Calbet et al 2007) and heterotrophic dinoflagellates (Levinsen et al 2000). Similar patterns in copepod feeding strategy were observed for the studied species in the White Sea.…”
Section: Discussionsupporting
confidence: 62%
“…This corresponds to the data from Cripps and Hill (1998), describing omnivorous feeding as more common in lowchlorophyll environments where copepods of the same genera usually ate the most abundant prey. In response to phytoplankton shortage, copepods may switch to alternate prey including nauplii (Tackx and Polk 1982), ciliates (Atkinson 1996), early developmental stages of other calanoids (Calbet et al 2007) and heterotrophic dinoflagellates (Levinsen et al 2000). Similar patterns in copepod feeding strategy were observed for the studied species in the White Sea.…”
Section: Discussionsupporting
confidence: 62%
“…The trophic interactions are particularly complex in subtropical coastal and estuarine environments where planktonic abundances, compositions and mesozooplankton feeding preferences are temporally variable because of dynamic hydrographic conditions (Gifford et al, 2007 and this study). Factors that regulating the feeding rates of mesozooplankton in dynamic environments generally include abundance of food items that affects the functional response of grazers, prey particle size and palatability that affects the feeding selectivity of grazers, characteristics of grazers (size and feeding behavior), physical environmental parameters (temperature and salinity) and turbulence (Kiørboe and Saiz, 1995;Båmstedt et al, 2000;Levinsen et al, 2000). Our result showed that mesozooplankton clearance rate (feeding rates per biomass) was FIGURE 8 | Mesozooplankton clearance rates on total phytoplankton community (Total) and phytoplankton with different sizes (Large: >20 µm; Middle: 2 ∼ 20 µm and 5 ∼ 20 µm in the first and the second sampling year, respectively; Small: <2 and <5 µm in the first and the second sampling year, respectively) at the two stations EO and WE.…”
Section: Discussion the Net Effect Of Mesozooplankton Feeding On Phytmentioning
confidence: 99%
“…Because most of the biomass increase was from large phytoplankton, specifically diatoms, this suggests a tight coupling between dinoflagellates and diatoms. Levinsen et al (2000) witnessed a similar increase of large microzooplankton in response to a coastal western Greenland diatom bloom, and suggested this coupling was also a result of top-down regulation: i.e. the high biomass of large microzooplankton within a diatom bloom might have resulted indirectly from increased abundance of diatoms, an alternate food source for macrozooplankton.…”
Section: Microzooplankton Grazing Biomass and Abundancementioning
confidence: 92%